Measuring the Unequal Gains from Trade * - Fajgelbaum, Pablo D.; Khandelwal, Amit K. (Quarterly Journal of Economics, 2016)
Individuals that consume different baskets of goods are differentially affected by relative price changes caused by international trade. We develop a methodology to measure the unequal gains from trade across consumers within countries. The approach requires data on aggregate expenditures and parameters estimated from a nonhomothetic gravity equation. We find that trade typically favors the poor, who concentrate spending in more traded sectors.